Computational mechanisms underlying multi-step planning deficits in methamphetamine use disorder - Claire A. Lavalley; Marishka M. Mehta; Samuel Taylor; Anne E. Chuning; Jennifer L. Stewart; Quentin J. M. Huys; Sahib S. Khalsa; Martin P. Paulus; Ryan Smith (Translational Psychiatry)
Abstract Current theories suggest individuals with methamphetamine use disorder (iMUDs) have difficulty considering long-term outcomes in decision-making, which could contribute to risk of relapse. Aversive interoceptive states (e.g., stress, withdrawal) are also known to increase this risk. The present study analyzed computational mechanisms of planning in iMUDs, and examined the potential impact of an aversive interoceptive state induction. A group of 40 iMUDs and 49 healthy participants completed two runs of a multi-step planning task, with and without an anxiogenic breathing resistance manipulation. Computational modeling revealed that iMUDs had selective difficulty identifying the best overall plan when this required enduring negative short-term outcomes – a mechanism referred to as aversive pruning. Increases in reported craving before and after the induction also predicted greater aversive pruning in iMUDs. These results highlight aversive pruning deficits as a novel mechanism that could promote poor choice in recovering iMUDs and create vulnerability to relapse.